Phonemic and semantic verbal fluency tasks: normative data for elderly Brazilians - Cristiane Silva Esteves; Camila Rosa Oliveira; Carmen Moret-Tatay; Esperanza Navarro-Pardo; Geraldo Atílio De Carli; Irenio Gomes Silva; Tatiana Quarti Irigaray; Irani Iracema de Lima Argimon (Psicologia: Reflexão e Crítica, 2015)
This study aims to investigate the influence of sociodemographic characteristics on the performance of older people on two tasks of verbal fluency and provide normative data for a Brazilian population of healthy elderly individuals with different educational levels. The initial sample included 521 individuals aged from 60 years, participating in the Program Family Health Strategy. Participants who had scores suggestive of cognitive decline on the Mini-Mental State Examination, depressive symptoms in Geriatric Depression Scale and self-reported neurological or psychiatric disorders were excluded. The final sample consisted of 218 participants in phonemic verbal fluency task (letters F, A and S) and 265 participants for semantic verbal fluency task (animals). The performance in both tests was associated with age and education, but not with sex. Still, the education variable was shown to have a greater impact on scores in phonemic and semantic tests than age in both forms of evocation. The results of this study suggest the importance of providing normative data for elderly Brazilians appropriate to age and education on verbal fluency tasks.